Plato's Arguments for Unity of Intelligent and Intelligible - Ali Owlanj; Said Binaye-Motlagh; Ali Karbasizadeh (Journal of Philosophical Investigations)
Unity of intelligent and intelligible has its supreme formation in philosophy of Mulla-Sadra. But this fact according to many philosophical texts is rooted in the philosophy of ancient Greek. For instance, it is recognizable in Plato, Aristotle and even Parmenides. Plotinus’s Enneads are ample of arguments about union of intelligent and intelligible and explanations and applications of this important philosophical principle. This essay tries to trace this principle in Plato by investigating his own texts. Of course, this is not going to be a kind of imposing Sadra’s philosophical views on Plato but rather to unveil common fundamental weltanschauungs and to show innate correlations and beyond-historical kinship of this philosophies. This essay tries to achieve this kinship in Plato by reconstructing his arguments for union of intelligent and intelligible and by this means contributes to study the historical development of this idea. To accept or deny the union of intelligent and intelligible makes important and meaningful divergences on reading and understanding Plato. The conclusions of Unity of intelligent and intelligible in interpreting plato’s Doctrines are discussing at the end with some instances.